Web-Based Incoming and Outgoing Mail Information System Using PHP and Mysql Programming Languages In Karanganyar Village - Rozaq Rais, Nendy Akbar (International Journal of Computer and Information System (IJCIS), 2022)
Information technology is currently developing rapidly, causing all aspects of human life to always be connected to the development of this technology. The influence of this technological development can be felt in various fields, both academic and non-academic. Manual data processing has begun to be eliminated and changed into a computerized system to facilitate the data processing process so that it can be done quickly and does not take a long time. Karanganyar Village Hall has a letter filing system that is still manual. Incoming letters are still stored in large folders that are sorted by letter number, in addition, archiving incoming letters requires the creation of a disposition to be addressed to the relevant party. The creation of this disposition awaits the leader who as a leader has a lot of busyness or activities. So that the process of making dispositions and making outgoing letters takes a long time. This Incoming and Outgoing Letter Application is one way to handle the processing of correspondence data starting from recording and archiving incoming letters, making dispositions, making outgoing letters, as well as reports of incoming and outgoing letters and is expected to be able to process correspondence data without taking a long time and can be processed. With this application, it is expected to make it easier for employees to manage correspondence. This application is built with PHP and MySQL.